Catalytic Asymmetric 1, 3‐Dipolar Cycloaddition of β‐Fluoroalkylated α, β‐Unsaturated 2‐Pyridylsulfones with Nitrones for Chiral Fluoroalkylated Isoxazolidines and γ‐Amino Alcohols. (9th January 2017) - Yang, Xing; Cheng, Feng; Kou, Ying‐Da; Pang, Shuai; Shen, Yong‐Cun; Huang, Yi‐Yong; Shibata, Norio
Abstract: 2‐Pyridylsulfone‐ and fluoroalkylated group‐activated olefins underwent highly efficient diastereo‐ and enantioselective 1, 3‐dipolar cycloadditions across various aromatic and aliphatic nitrones in the presence of a chiral Ni II /bis(oxazoline) catalyst. The process was tuned by 4 Å molecular sieves, chiral bis(oxazoline) ligands, reaction solvents, and temperature. A wide array of optically pure fluoroalkylated isoxazolidines were obtained, thus facilitating the asymmetric synthesis of an enantioenriched α‐trifluoromethylated γ‐amino alcohol in gram‐scale and a trifluoromethylated derivative of 1, 3‐oxazinan‐2‐one with potential pharmaceutical interest. A stereochemical model, based on the absolute configuration of one adduct and some control experiments, was postulated to account for the observed endo‐ and enantioselectivity.